THE MALE NORMAL SCHOOL OF LIMA, PREDECESSOR OF THE NATIONAL UNIVERSITY OF EDUCATION LA CANTUTA, MEETS 108 YEARS OF ITS REVIVAL - Aguilar Berrospi, David (2014)
In the late nineteenth and early twentieth century, it was the golden age of the old Peruvian oligarchy. Under the impetus of an extraordinary commercial revitalization, owns a fraction linked to the export, finance, trade and speculation organize politically managed nationally. Increase political importance take over of state apparatus: Government, Parliament, Judiciary, University, etc. Jorge Basadre called aristocratic republic. During this time, José Pardo called educational reform passed during management of his father Manuel Pardo in 1876, to enact laws N ‘74 and No. 162 of November 27 th and December 5th 1905 respectively. On 14 May 1905 opened Normal School for Boys, predecessor of UNE, La Cantuta, in temporary premises was granted in Corcobado Street, located in Lima Down Town. Ceremony was attended by President of the Republic, Dr. José Pardo y Barreda, Minister of Education Dr. Jorge Polar and Acting Principal , Dr. Isidoro Poiry. Enrique Guzmán y Valle, in April 1909 he was appointed professor at Ecole Normale. In 1915 he was appointed Principal at School until his death in 1923.